Tindak Tutur Ilokusioner Ekspresif Plesetan Nama Kota di Jawa Tengah: Kajian Pragmatik - Hari Kusmanto (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study aims to explore the forms of expressive speech acts that play on the names of cities in Central Java. The data in this study is a play on the names of the cities in Central Java that are expressively valued. The data source in this study is a play on the names of Cities in Central Java. Data collection in this study uses the documentation method, and see continued recording techniques. Analysis of the data in this study uses the intralingual equivalent method. The results of this study indicate that the play on the names of Cities in Central Java is expressed with expressions of sadness, happiness, disappointment, complaining, convincing, hope, forgiveness, praise, and criticism. The most widely used expressive speech act is sadness expression. This shows that many speakers experience a sad experience.